Monetary Regimes and External Shocks Reaction: Empirical Investigations on Eastern European Economies - Muhammad Khan; Nikolay Nenovsky (Romanian Economic Journal, 2017)
In the late 90's, after severe financial crisis, accompanied by inflation and exchange rate instability, Eastern Europe emerged into two radically contrasting monetary regimes (Currency Boards and Inflation targeting). The task of our study is to compare econometrically the performance of these two regimes in terms of their resilience to the external real and nominal shocks, coming from Euro area. In other words, we test the non-neutrality of exchange rate regimes with respect to these connections. Our PVAR model results reveal that the choice of monetary regimes indeed determines the ability of a country to absorb the external shocks.